Initial point for enhancing DC Programming and DCA in Physical Layer Security - Tuan, Nguyen Nhu (Journal of Science and Technology on Information security, 2023)
Abstract— Physical layer security (PLS) is to enable confidential data transmission through wireless communication systems in the presence of illegitimate receivers, without basing on higher-layer encryption. The goal of PLS is to make use of the properties of the physical to enable critical aspects of secure communication. PLS's additional strength is that it is based on information-theoretic security, which assumes no limit on the opponent's computational power and is thus inherently quantum-resistant. In general, PLS problems are non-convex programming and thus hard to deal with. One approach to handling these problems is based on DC programming and DCA, in which finding a good initial point of DCA scheme is still a complicated, challenging and open problem. This paper proposal some good initial points for the PLS problem DCA-DF scheme on Decode-and-Forward relaying wireless networks.